Bili Bante Tourism Potential as a Sustainable Tourism Destination: Strategy and Challenge Study - Titik Ceriyani Miswaty; Bagas Anggara; Muhammad Taufik; Muharis Muharis; Lativa Nur (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This study explores the potential of community-based tourism in Bili Bante, including aspects of natural beauty, cultural diversity, and ecotourism. The observations show that around 75% of the tourist areas in Bili Bante are still preserved with minimal environmental pollution, making it a potential destination for ecotourism development. In addition, the cultural diversity of the local community, including traditional traditions, traditional music, and handicrafts, can be a strong tourist attraction. The interviews with local people revealed that 60% support the development of community-based tourism to improve the local economy, although 40% are concerned about the negative impacts on the environment if tourism management is not carried out carefully. The main obstacles identified are inadequate infrastructure and lack of destination promotion. Based on these findings, this study recommends increasing investment in infrastructure development, training for local people, and developing more effective marketing strategies. In addition, clear regulations regarding natural resource management and environmental conservation must be enforced to support the sustainability of tourism development in Bili Bante.